Wolfgang Koeppens auseinandersetzung mit der tradition: aspekte der intertextualitÃ¤t in der so genannten nachkriegs" trilogie - Weber, Undine S (Rhodes University, Faculty of Humanities, School of Languages, 2015)
Wolfgang Koeppen's three post" war novels have often been called a trilogy, purely based on their publication in rapid succession in the early 1950s. This study establishes a connection between the works by looking at their roots in Irish, Anglo" American, French and German modernism, and shows up links between Wolfgang Koeppen, James Joyce, E.E. Cummings, Charles Baudelaire and Thomas Mann. This comparative analysis concludes, by integrating socio" political factors of life in West Germany after World War II, that Koeppen transcends the modernist tradition "“ the fact that modernism has become tradition, i.e. it has become "classic" , in contradiction to being "modern" . Koeppen's texts do not only allude to and build on classic texts and refer to stylistic and narrative modernist elements such as stream" of" consciousness and sketching a fragmented society in turmoil; the very act of recurring to myths and texts of the Western canon in order to depict the disaffected individual is an almost post" modern one.
Keywords: Koeppen, Wolfgang, 1906-1996 -- Criticism and interpretation; Koeppen, Wolfgang, 1906-1996 -- Works -- 1986; German fiction -- 20th century -- History and criticism